Analisis Indeksikalitas Dalam Pemaknaan Pembiayaan Hunian Syariah di PT. X Developer & Kontraktor Syari’ah: Analisis Indeksikalitas Dalam Pemaknaan Pembiayaan Hunian Syariah di PT. X Developer & Kontraktor Syari’ah - Sa'adiyah, Halimatus; Eferyn, Krissantina (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Indexicality Analysis in the Meaning of Shariah Sharia Residential Financing at PT. X Developer & Shari'ah Contractor. One of the businesses in Indonesia that currently uses the concept of Shariah is a residential business. This research aims to understand the meaning of Shariah on sharia financing. Through Islamic ethnometodology as a qualitative approach, analysis is carried out to obtain the empirical meaning of Sharia financing by business people. The final stage in the research is a comparative study between the findings and the foundation of the Qur'an and sunnah to determine whether residential financing has fulfilled sharia rules or not sharia. The results of this study show that the meaning of sharia residential financing is diverse. On a practical level, sharia means ease and absence of fines, while at the ideological level the meaning of financing is more divine, namely the fulfillment of the agreement and stay away from God's prohibition to avoid the sin of riba